2010
DOI: 10.1016/j.watres.2010.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation for improved recovery of anaerobic digesters after toxicant exposure

Abstract: Abstract:Bioaugmentation was investigated as a method to decrease the recovery period of anaerobic digesters exposed to a transient toxic event. Two sets of laboratory-scale digesters (SRT = 10 days, OLR = 2 g COD/Lday),started with inoculum from a digester stabilizing synthetic municipal wastewater solids (MW) and synthetic industrial wastewater (WW), respectively, were transiently exposed to the model toxicant, oxygen.Bioaugmented digesters received 1.2 g VSS/L-day of an H2-utilizing culture NOT THE PUBLISHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…Total solids and VS concentration and COD were measured by standard methods (APHA, AWWA, WEF, 1999). VFA concentrations were determined by gas chromatography flame ionization detection (GC-FID) after samples were centrifuged, supernatant filtered through 0.45 µm syringe-tip filter, and acidified with phosphoric acid (Schauer-Gimenez et al, 2010). Since accurate bioplastic COD analysis was not achievable, the bioplastics ThOD values were calculated based on the bioplastic mass and molecular structure, with ratios of 1.67 g ThOD/g PHB and 1.33 g ThOD/g PLA.…”
Section: Analysesmentioning
confidence: 99%
“…Total solids and VS concentration and COD were measured by standard methods (APHA, AWWA, WEF, 1999). VFA concentrations were determined by gas chromatography flame ionization detection (GC-FID) after samples were centrifuged, supernatant filtered through 0.45 µm syringe-tip filter, and acidified with phosphoric acid (Schauer-Gimenez et al, 2010). Since accurate bioplastic COD analysis was not achievable, the bioplastics ThOD values were calculated based on the bioplastic mass and molecular structure, with ratios of 1.67 g ThOD/g PHB and 1.33 g ThOD/g PLA.…”
Section: Analysesmentioning
confidence: 99%
“…Thus, based also on findings in previous studies (Fotidis et al 2013a), it is possible to introduce SAO-HM pathway in a digester by controlling the ammonia levels as long as a ''critical biomass'' of ammonia-tolerant fast-growing methanogenic consortium is present. If ammonia-tolerant consortia are not present, a technical approach to overcome ammonia inhibitions could be bioaugmentation (Schauer-Gimenez et al 2010) of ammonia-tolerant methanogenic consortia in anaerobic digesters operating under high ammonia levels. Unfortunately, this has not been demonstrated yet.…”
Section: Dominant Acetate Degradation Pathway and Methanogenic Populamentioning
confidence: 99%
“…Chouari et al (2005) reported that the enrichment of WCHA1-57 (ARC I) phylotypes in cultivations using formate or H 2 /CO 2 as substrates, which are typical substrates for methanogenic archaea, although the methane production of the enrichments was not checked in the literature. In addition, many WCHA1-57-related 16S rRNA gene sequences have been retrieved from anaerobic digesters (Chouari et al, 2005;Steinberg and Regan, 2008;Rivière et al, 2009;Schauer-Gimenez et al, 2010). In some anaerobic digesters treating municipal sewage sludge, the WCHA1-57 phylotype population represented one of the predominant archaeal components, and the relative clonal abundance was > 70% in the archaeal clone libraries (Chouari et al, 2005;Rivière et al, 2009).…”
Section: Results and Discussion Exploration Of Taxonomically Novel Mementioning
confidence: 99%